Ieo Evaluation Report IMF Technical Assistance 2005. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2005)
This evaluation examines the technical assistance (TA) provided by the IMF to its member countries. The evaluation is based on desk reviews of a broad sample of countries, analyses of cross-country data on TA, six in-depth country case studies, reviews of past evaluations, and interviews with IMF staff and other stakeholders. The objective of the IMF TA is to contribute to the development of the productive resources of member countries by enhancing the effectiveness of economic policy and financial management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet